2013
DOI: 10.4317/medoral.18713
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural changes in dentine caused by endodontic irrigants

Abstract: Objective: To study nanostructural dentinal changes produced by endodontic irrigants. Study Design: Experimental study. Nanoindentations were performed on peritubular (PD) and intertubular dentine (ID) with an atomic force microscopy. Stiffness and adhesion force were determined before and after application of 5.25% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA). Normalized differences before and after treatment for stiffness and adhesion forces were calculated. A paired T-test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…It has been known for some time that varying concentrations of chelating agents, such as EDTA, acids, and disinfecting agents such as sodium hypochlorite (NaOCl), have demonstrated an ability to undermine dentin microhardness and elasticity (60)(61)(62)(63), while a more recent study has reported that dentin subject to prolonged calcium hydroxide (CaOH) exposure, demonstrates a decreased resistance to fracture (162).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known for some time that varying concentrations of chelating agents, such as EDTA, acids, and disinfecting agents such as sodium hypochlorite (NaOCl), have demonstrated an ability to undermine dentin microhardness and elasticity (60)(61)(62)(63), while a more recent study has reported that dentin subject to prolonged calcium hydroxide (CaOH) exposure, demonstrates a decreased resistance to fracture (162).…”
Section: Discussionmentioning
confidence: 99%
“…The use of 5.25% NaOCl has been reported to decrease Young's modulus of dentin, in addition to its flexural stress (62). Reduction in dentin elasticity after treatment with NaOCl has also been reported (60,61,63). This may be due to the dissolution of the organic component of the dentin by NaOCl.…”
Section: Ultrastructural Changes To Dentin Following Iatrogenic Procementioning
confidence: 99%
See 1 more Smart Citation
“…Perubahan rasio kalsium-fosfat (Ca/P) di dentin dinding saluran akar oleh EDTA juga dapat merubah proporsi komponen organik dan inorganik yang berdampak mempengaruhi kekerasan, permeabilitas serta solubilitas dentin. 7 Sumber EDTA juga tidak dijumpai secara alamiah sehingga dianggap sebagai polutan. Mengingat masih dijumpainya kelemahan dari bahan irigasi NaOCL dan EDTA tersebut di atas, masih perlu dicari dan dikembangkan alternatif bahan irigasi yang bersifat biokompatibel, efektif dan aman sehingga dapat meminimalisasi dampak yang merugikan struktur gigi maupun jaringan periapikal.…”
Section: Pendahuluanunclassified
“…Generally, the hardness test can serve as an indirect method for measuring how well the materials have set. For example, higher values of hardness are indicative of more extensive polymerization of dental resins (Barón et al ., ). It has been reported that disinfection agents, especially peroxide‐based lubricants and NaOCl, can adversely affect the setting of resins that cure by a free‐radical polymerization mechanism (Onay et al ., ) and may indirectly affect surface hardness of resin‐based sealers.…”
Section: Introductionmentioning
confidence: 97%